The Effect of Family Support and Social Support on The Incidence of Postpartum Depression - Estiningtyas Estiningtyas; Anindhita Yudha Cahyaningtyas; Sri Sugiarsi (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Postpartum depression (PPD) is a severe complication of labour where there are significant adverse effects on the mother and infant. In general, PPD occurs in the 4-6 weeks after delivery. Family and social support are needed by mothers to cope with stress during the postpartum period caused by sudden hormonal changes that influence mood swings, domestic workload, and caring for infant and mother during the postpartum period, resulting in fatigue and lack of sleep. The purpose of the study was to analyze the effect of family and social support on PPD occurrence.This study used an analytic observational research design with a cross-sectional approach. This study's population was postpartum mothers at 0-6 weeks in the Health Agency of Sukoharjo Regency work area. The sampling technique used Multistage Random Sampling with a sample size of 160 respondents. The instruments used were the family support questionnaire, social support, and EPDS (Edinburgh Postnatal Depression Scale). Data analysis was using logistic regression and Odd Ratio. The results of the analysis of family support data are P-value 0.027 <(0.05) and OR value 5.787, and social support P-value 0.025 <(0.05) and OR value 5.693. The P-value result means that there is a significant effect of family support and social support on the occurrence of PPD where mothers who lack family and social support will be at risk to experience PPD, with each risk 5.787 times higher and 5.693 times higher, respectively. Health workers are expected to emphasize the importance of family and social support for postpartum mothers in emotional support and technical support by helping postpartum mothers take care of infants, self-care, and homework to reduce the risk of postpartum depression. Keywords: Depression, social support, family support